Nurses in China lack knowledge of inhaler devices: A cross-sectional study - Xie, Ning; Zheng, Zheng; Yang, Qilian; Li, Man; Ye, Xiaofen (Frontiers in Pharmacology, 2023)
ABSTRACT Objective: To know the knowledge on inhaler devices in medical staff, this study surveyed knowledge of inhaled therapy and the use of inhaler devices in nurses in China. Methods: 1831 nurses were selected to survey on a new self-designed questionnaire online. The questionnaire has 11 questions, including the storage location of the inhaler devices, steps of using the inhaler device, and the common errors when using various devices, etc. Results: Among the 1831 participants, 816(44.57%), 122(6.66%) and 893(48.77%) nurses worked in community hospital, secondary hospital and tertiary hospital respectively. Adequate knowledge of inhaler devices was demonstrated by nurses working in community hospital(20.10%)、Secondary hospital(8.2%) and Tertiary hospital(13.1%). 27.70% nurses in community hospital knew operational key points in using inhaler compared to in secondary hospital (15.57%) and tertiary hospital (23.18%) P<0.01. Only 9.5%-26.00% of participants chose correct answers about the ten questions about the use of inhaler. The accurate rate of the questions is generally low with the highest percentage 26.00%. Conclusion: Inhalation knowledge of nurses in community hospital is better than other high-level hospital. It due to the clearer division in work and increasing workload. Inhalation knowledge of nurses is in a low level Overall. And knowledge on inhaler devices should be strengthen among nurses in hospital China. It is necessary to create training opportunities for nurses to increase their awareness and knowledge of chronic respiratory diseases management.